2020
DOI: 10.1007/s11695-020-04555-8
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss After Bariatric Surgery in Morbidly Obese End-Stage Kidney Disease Patients as Preparation for Kidney Transplantation. Matched Pair Analysis in a High-Volume Bariatric and Transplant Center

Abstract: Background The number of morbidly obese kidney transplant candidates is growing. They have limited access to kidney transplantation and are at a higher risk of postoperative complications. Bariatric surgery is considered as a safe weight loss method in those patients. Objectives Matched pair analysis was designed to analyze the preparatory and postoperative weight loss after bariatric procedures in end-stage kidney disease (ESKD) and non-ESKD morbidly obese patients. Methods Twenty patients with ESKD underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…SG in ESKD patients is not related to higher risk of leaks, reoperations, or mortality in 1 year follow-up [59]. Our center morbidly obese ESKD patients have similar weight loss results after bariatric procedure than non-ESKD [42,44]. Nine of twenty of them underwent kidney transplantation without any perioperative complications and with good kidney function in follow-up.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…SG in ESKD patients is not related to higher risk of leaks, reoperations, or mortality in 1 year follow-up [59]. Our center morbidly obese ESKD patients have similar weight loss results after bariatric procedure than non-ESKD [42,44]. Nine of twenty of them underwent kidney transplantation without any perioperative complications and with good kidney function in follow-up.…”
Section: Discussionmentioning
confidence: 60%
“…Two bariatric procedures were preferred [23,40]. LSG (laparoscopic sleeve gastrectomy) and LRYGB (laparoscopic roux-en-y gastric bypass) appear to cause effective weight-loss before KT and improve surgical access during transplantation [41][42]. Uncertainties exist regarding optimal timing of bariatric surgery [38].…”
Section: Discussionmentioning
confidence: 99%
“…There is also much interest in the possibility of bariatric surgery in either potential renal transplant candidates or post-renal transplant [ 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. Several studies have shown that bariatric surgery is safe and feasible in patients with ESKD and kidney transplant recipients [ 133 , 138 ].…”
Section: Obesitymentioning
confidence: 99%
“…Outcomes following sleeve gastrectomy (SG) were reported in 20 studies, 20,21,23,24,26,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] gastric bypass (GB) in 17 studies, [19][20][21][22][23][24][25][27][28][29][30]33,[35][36][37]41,42 adjustable gastric banding (AGB) in 10 studies, [20][21][22][23][27][28][29][30]33,41 and duodenal switch in two studies. 22,41 Fifteen studies reported on multiple bariatric surgery techniques.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…22,41 Fifteen studies reported on multiple bariatric surgery techniques. [20][21][22][23][24][27][28][29][30]33,[35][36][37]41,42 Overall complication rates were low, although there was variability among studies (Table 5). Complication rates in people with ESKD did not differ from the control population in three studies, 21,23,40 but…”
Section: Bariatric Surgerymentioning
confidence: 99%